Pengaruh Atap Tritisan Pada Rumah Tinggal Villa Mutiara sebagai upaya penerapan Konsep Arsitektur Tropis - Husnirrahman Jamaluddin; Tri Amartha Wiranata; Ahmad Nadhil Edar (Universitas Muslim Indonesia, 2026)
Indonesia’s tropical climate, characterized by high solar radiation, humidity, and rainfall, necessitates climate-responsive design strategies in residential buildings. However, the growing trend of minimalist housing often neglects passive design elements, particularly roof overhangs (tritisan), resulting in reduced thermal and visual comfort. This study aims to evaluate the effect of tritisan dimensions on daylight performance and indoor thermal conditions in residential buildings located in Villa Mutiara. A qualitative-descriptive method was employed, combining field observations, visual documentation, and literature review on tropical architecture and daylighting. The analysis focused on the relationship between opening dimensions, overhang size, and their impact on solar exposure and indoor comfort. The findings indicate that insufficient overhang dimensions, particularly those around 20 cm, are ineffective in blocking direct solar radiation and rain penetration. This condition leads to excessive heat gain and glare, especially in buildings with large glass openings. The study suggests that optimal tritisan dimensions should be at least 30% of the opening height to improve shading performance. These results highlight the importance of integrating overhang design as a passive strategy to enhance comfort and energy efficiency in tropical housing.